Preparation and Antimicrobial Screeningof Cu (II), Ni (II), Zn (II) Cd (II) Complexes - R. M. Desai; M. K. Shah; V. H. Shah (E-Journal of Chemistry)
The metal complexes of Ni(II), Cu(II), Zn(II) Cd(II) with organic ligands viz Hydrazine hydrate, 1,2-N,N'-Bisammonium thiocarbamoyl ethane and 1,4-N,N'-Bisammonium thiocarbamoyl benzene have been prepared. These ligands and metal complexes of dithiocarbamates were screened for their antimicrobial activity against various microbs.